2017
DOI: 10.18203/2394-6040.ijcmph20175509
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of occupational health hazards in districts health facilities in Kigali, Rwanda

Abstract: Background: Health workers are constantly exposed to chemical, physical, psychological and biological agents that affect their health. Regular information is critical for setting priorities necessary to enhance workers health and safety. The study determined the occurrence of occupational health hazards among health care worker in the three selected district health facilities in Kigali, Rwanda (July-December 2016).Methods: It adopted a cross-sectional design involving both qualitative and quantitative data col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…These values compared to studies carried out in other developing countries using varying validated and standardized assessment instrument were higher. Nwankwo et al 23. observed a prevalence rate of psychosocial stress among Rwandan health-care workers at 15.3%, whereas Alhassan and Poku found that Ghanaian health-care workers had a psychosocial stress prevalence rate of 17% 24.…”
Section: Discussionmentioning
confidence: 99%
“…These values compared to studies carried out in other developing countries using varying validated and standardized assessment instrument were higher. Nwankwo et al 23. observed a prevalence rate of psychosocial stress among Rwandan health-care workers at 15.3%, whereas Alhassan and Poku found that Ghanaian health-care workers had a psychosocial stress prevalence rate of 17% 24.…”
Section: Discussionmentioning
confidence: 99%
“…Refers to an act that endangers the well-being of health workers if they are exposed to their physical body parts in their working environment, which could impose their lives at risk and pose a greater threat to their security and safety in their future life[ 19 ].…”
Section: Methodsmentioning
confidence: 99%